National monitoring of antibiotic resistance of pathogens causing community-acquired urinary tract infections in Russia: results of the multicenter epidemiological study «DARMIS -2023» - Kozlov R.S.; Palagin I.S.; Ivanchik N.V.; Trushin I.V.; Dekhnich A.V.; Edelstein M.V.; Perepanova T.S.; Belashova M.A.; Nastausheva T.L.; Ivanova I.A.; Valiullina I.R.; Momotova A.A.; et al. (Клиническая микробиология и антимикробная химиотерапия)
Objective.